MEDICAL REHABILITATION MANAGEMENT OF CARPAL TUNNEL SYNDROME - Imam Subadi; Hanik Hidayati; Fidiana Fidiana; Nur Sulastri (Journal of Pain, Headache and Vertigo, 2021)
Carpal tunnel syndrome (CTS), the most common entrapment neuropathy in the upper extrimity, is a clinical syndrome characterized by a tingling sensation, numbness, pain, or weakness in the hand and wrist radiating up to the arm. This condition is a major cause of absenteeism, reduced productivity, and financial loss among various neuropathy due to median nerve compression. This paper, medical rehabilitation of CTS is viewed. Medical rehabilitation of CTS aimed to reduce pain, reduce clamping of the carpal tunnel, sensory and motor reeducation so that hand function improves and can perform activities of daily living. Treatment options can be given includes exercise therapy, ultrasound diathermy, low level laser therapy (LLLT), and shock wave therapy (SWT).